(untitled) (GESTIÓN Y TENDENCIAS, 2021)
The global COVID-19 pandemic and its significant social and economic consequences have created a new scenario of uncertainty for companies and entrepreneurs. This situation can be addressed through the implementation of innovative digital transformation projects grounded in the strategic reconfiguration of an organization’s existing dynamic capabilities, for which specific recommendations are offered.